Compositional interaction design—changes in design practice and its implications for teaching and research. Issue 1 (2nd January 2020) - Stolterman, Erik; Wiberg, Mikael
ABSTRACT: In this article, we focus on compositional interaction design as an emergent professional practice in interaction design. We propose that compositional interaction design practice can be defined as a practice of knowing, mapping configuring, customizing and connecting elements to form larger compositional wholes. We demonstrate how this practice demands new compositional skills, new methods and a changed division of labours. We suggest that this contemporary practice can be understood in terms of how different computational components are integrated to form interactive products and services. We illustrate this new practice with two concrete examples. Our first example illustrates compositional interaction design at a small scale, whereas our second example illustrates compositional design at a larger scale. We also discuss how this emergent practice relates to other streams of development (e.g. craft-oriented HCI and human-centred design) and we discuss what implications this shift may have to interaction design educational programs aimed at preparing students for this emerging professional practice.